Fermentation of Cellulose to Methane and Carbon Dioxide by a Rumen Anaerobic Fungus in a Triculture with Methanobrevibacter sp. Strain RA1 and Methanosarcina barkeri - Mountfort, Douglas O. (1982)
The fermentation of cellulose by a rumen anaerobic fungus in the presence of Methanobrevibacter sp. strain RA1 and Methanosarcina barkeri strain 227 resulted in the formation of 2 mol each of methane and carbon dioxide per mol of hexose fermented. Coculture of the fungus with either Methanobrevibacter sp. or M. barkeri produced 0.6 and 1.3 mol of methane per mol of hexose, respectively. Acetate, formate, ethanol, hydrogen, and lactate, which are major end products of cellulose fermentation by the fungus alone, were either absent or present in very low quantities at the end of the triculture fermentation (≤0.08 mol per mol of hexose fermented). During the time course of cellulose fermentation by the triculture, hydrogen was not detected (<1 × 10(−5) atm; <0.001 kPa) and only acetate exhibited transitory accumulation; the maximum was equivalent to 1.4 mol per mol of hexose at 6 days which was higher than the total acetate yield of 0.73 in the fungus monoculture. The effect of methanogens is interpreted as a shift in the flow of electrons away from the formation of electron sink products lactate and ethanol to methane via hydrogen, favoring an increase in acetate, which is in turn converted to methane and carbon dioxide by M. barkeri. The maximum rate of cellulose degradation in the triculture (3 mg/ml per day) was faster than previously reported for bacterial cocultures and within 16 days degradation was complete. The triculture was used successfully also in the production of methane from cellulose in the plant fibrous materials, sisal (fiber from leaves of Agave sisalona L.) and barley straw leaf.